Kajian program kesehatan jiwa masyarakat di puskesmas Kota Kotamobagu - Sitorus, John J. T. A.; Ratag, Gustaaf A.E.; Siagian, Iyonne E. T. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2019)
Mental health is defined as a state of well-being where an individual realizes his own potential, can cope with the stress of life, work productively, and is able to actively contribute to society. This study aims to provide an overview of the mental health programs in primary healthcare centers in Kotamobagu. The research design used is a cross-sectional descriptive approach. This study is conducted on all primary healthcare facilities operating in the area of Kotamobagu during October 2019. The study shows that the mental health program running in Kotamobagu is still not optimal. Mental Health Service Programs in primary healthcare facilities in the city of kotamobagu is still not optimal due to the lack of training and funding However the city of Kotamobagu shows promise as it already has a strong foundation to build upon it’s dutiful healthcare providers and an active mobile team.Keywords: Mental healthcare programs, Kotamobagu